2021
DOI: 10.1101/2021.10.26.466006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upregulated PD-1 Signaling is an Important Antagonist to Glomerular Health in Aged Kidneys

Abstract: Kidney aging and its contribution to disease and its underlying mechanisms are not well understood. With an aging population, kidney health becomes an important medical and socioeconomic factor. We previously showed that podocytes isolated from aged mice exhibit increased expression of Programed Cell Death Protein 1 (PD-1) surface receptor and its two ligands (PD-L1, PD-L2). PDCD1 transcript increases with age in micro-dissected human glomeruli, which correlates with lower eGFR, and higher segmental glomerulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
2
0
0
Order By: Relevance
“…Tubular PD-L1 positivity was predominantly found in proximal tubular epithelial cells as previously described ( 12 , 13 ). Glomerular PD-L1 was found in parietal epithelial cells and podocytes, again in line with previous reports ( 14 ). Among potential mechanisms, tubular PD-L1 positivity was positively correlated with systemic inflammation (elevated serum levels of CRP), in line with previous investigations reporting CRP serum elevation to reflect irAE onset including kidney involvement ( 15 , 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…Tubular PD-L1 positivity was predominantly found in proximal tubular epithelial cells as previously described ( 12 , 13 ). Glomerular PD-L1 was found in parietal epithelial cells and podocytes, again in line with previous reports ( 14 ). Among potential mechanisms, tubular PD-L1 positivity was positively correlated with systemic inflammation (elevated serum levels of CRP), in line with previous investigations reporting CRP serum elevation to reflect irAE onset including kidney involvement ( 15 , 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…In AD patients and mouse models, PD-1 expression was upregulated in astrocytes and microglia (Kummer et al, 2021). In addition, a recent study found that enhanced expression of PD-1 was highly correlated with reduced kidney function in aging humans (Pippin et al, 2022). In our study, PD-1/ PD-L1 pathway activity was significantly enhanced in the aging (64-week-old) hippocampus at both the methylation and transcriptional levels.…”
Section: Discussionsupporting
confidence: 67%